2014
DOI: 10.4103/0972-2327.128547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and long-term outcome of surgery for hypothalamic hamartoma in children with refractory epilepsy

Abstract: Context:Hypothalamic hamartomas (HH) are ectopic masses of neuronal and glial tissue most commonly presenting with medically refractory gelastic seizures with evolution to other seizure types. They are also associated with cognitive and behavioral problems to varying extent. Surgery has been found to improve quality of life in more than 50% of patients.Aim:To evaluate the clinical characteristics and long-term outcome of surgery in children with HH and refractory epilepsy.Materials and Methods:A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…4 Pterional skull base approaches have yielded some success for treatment of hypothalamic hamartomas, however, access to the hypothalamus can be limited through this approach. 11,27,15 Noteably, Drees, et al, reported a mean resection of 64% in 10 patients treated with transcallosal or endoscopic-pterional/endoscopic-FTOZ approaches; it was noted that giant HH led to signi cant di culty in obtaining a complete resection. No patients experienced seizure freedom.…”
Section: Microsurgical Resectionmentioning
confidence: 99%
“…4 Pterional skull base approaches have yielded some success for treatment of hypothalamic hamartomas, however, access to the hypothalamus can be limited through this approach. 11,27,15 Noteably, Drees, et al, reported a mean resection of 64% in 10 patients treated with transcallosal or endoscopic-pterional/endoscopic-FTOZ approaches; it was noted that giant HH led to signi cant di culty in obtaining a complete resection. No patients experienced seizure freedom.…”
Section: Microsurgical Resectionmentioning
confidence: 99%
“…Furthermore, surgical resection is safe with a favorable outcome of epilepsy in 50 % with significant improvement in behavior and marginal change in cognitive functions. The reasons for thinking that HH with GS play a major role on development [36] and behavior lie in the following considerations. These children with HH usually have no history of retarded or abnormal development before the onset of GS.…”
Section: Cognitive Malfunctionsmentioning
confidence: 99%
“…Refractory epilepsy related to behavioral and cognitive dysfunction may be the most common presentation of HH. Open surgical resection is safe with a favorable outcome of epilepsy in 50 % with significant improvement in behavior and marginal change in cognitive functions [36].…”
Section: Behavior Disordermentioning
confidence: 99%
“…It is estimated that it achieves seizure control in 50% of cases, with improvement in behaviour and cognition. 1,5 Several studies have demonstrated the efficacy of stereotactic radiosurgery (gamma-knife surgery), with outcomes similar to those of conventional surgery and decreased morbidity and mortality, 1,6 with the downside that its effects show later (6 months post-surgery) and that sometimes several interventions are required to achieve adequate symptom control. …”
Section: Formas De Presentación Clínica Del Hamartoma Hipotalámicomentioning
confidence: 99%